When there is no air, the cradle will fall: A narrative review of tobacco-related content across infant safe sleep interventions - Jawed, Aysha; Jassal, Mandeep (Frontiers in Pediatrics, 2022)
Sudden Unexpected Infant Death (SUID) from sleep-related causes is a leading cause of infant mortality worldwide. Sudden Infant Death Syndrome (SIDS) is one of the primary causes of SUID attributed to one or more environmental or behavioral determinants surrounding safe sleep practices among infants. The focus of many interventions on mitigating SIDS have addressed visible determinants pertaining to bed sharing, safe sleep surfaces, and removal of blankets, toys and other choking or strangulation hazards. Tobacco reduction and cessation have not been at the heart of any infant safe sleep interventions although addressing tobacco exposure is one of the primary safe sleep recommendations of the American Academy of Pediatrics. To date, there has not been a comprehensive review published on tobacco-related components across safe sleep interventions to reduce the risk of SIDS as the basis to contribute towards decreasing the rate of infant mortality. This review synthesizes the best practices, strategies, education, and additional interventions centered on addressing tobacco exposure as a risk factor for SIDS. Ten peer-reviewed studies were identified between 1995 to 2021 and integrated into this narrative review. There were three cross-sectional studies, three campaigns, one multi-center case control study, two randomized controlled trials, and two group comparison studies. Strengths and limitations of each approach are delineated followed by recommendations for future campaign, research, program, and practice endeavors to account for the totality of pertinent modifiable risk factors that contribute towards heightened infant mortality from SIDS.